Role of Resuscitation Promoting Factor-like Protein from Nocardiopsis halophila - Yufan Zhang; Jingjing Liu; Min Cao; Yujia Zhang; Xiumin Zhang (Microorganisms, 2023)
Resuscitation promoting factors (Rpf), a class of proteins secreted by gram-positive bacteria including actinobacteria, promote the resuscitation of dormant bacteria and spore germination. Here, we describe the reconstitution of the resuscitation promoting activity of the Rpf protein from Nocardiopsis halophila CGMCC 4.1195T in vitro and in vivo. The Rpf protein was expressed in the host Escherichia coli BL21 codon plus (DE3) and was confirmed to have a significant resuscitation effect on the viable but non-culturable (VBNC) N. halophila. Subsequently, the rpf gene of N. halophila was knocked out. We found that the growth rate of the mutant strain (Δrpf) was slower than that of the wild strain, and the former produced significantly shorter spores than the wild-type strain. Our results confirmed the activity of the Rpf protein in N. halophila to promote dormant bacteria resuscitation. This study will lay the foundation for the application of the Rpf protein from N. halophila to exploit actinomycetes resources.